Five must-visit destinations in Karakalpakstan - Bekbosinov Yesbosin Bekpolatovich (Global Scientific Publishing, 2023)
Karakalpakstan has many interesting destinations for tourists. On the one hand, this country is in the center of attention of the world public because of the ecological crisis, but on the other hand, it has attracted the attention of many people with its rich history, achievements, cultural heritage objects and architectural monuments.
Keywords: Ayoz Castle; Karakalpakstan; Ship Graveyard; Sulayman Bakirgani